Zmiany systemu wyborczego a wyniki wyborów do organu stanowiącego gmin na przykładzie województwa pomorskiego - Uziębło, Piotr (Polityka i Społeczeństwo, 2021)
This Article should answer questions related to the practical application of the Electoral Code solutions related to the electoral system to the constitutive organs of the communes. The basic idea is whether the majority system significantly changed the composition of these organs in those communes of over 20,000 inhabitants, as well as the effects of the modifications brought about in shaping constituencies in cities with county rights. The research was carried out on the example of the twenty communes of the Pomeranian Voivodship. The results can hardly be considered optimistic. The use of single-seat constituencies made worse the representativeness of organs which, to a large extent, lead to over-representation of the strongest political or local groups in the various communes. The system also did not lead to an increase in the number of independent councillors. The situation in the councils of cities with county rights remained almost the same. Introducing the possibility of creating larger constituencies was not reflected in practice. All cities have maintained the current size of the constituencies, which in combination with the d'Hondt method, eliminated the representatives of smaller electoral committees from the composition of councils or marginalized the position of those representatives.